Photo-Oxidation of Water Using Nanocrystalline Tungsten Oxide under Visible Light - J. W. J. Hamilton; J. A. Byrne; P. S. M. Dunlop; N. M. D. Brown (International Journal of Photoenergy)
The photoelectrolysis of water to yield hydrogen and oxygen using visible light has enormous potential for solar energy harvesting if suitable photoelectrode materials can be developed. Few of the materials with a band gap suitable for visible light activation have the necessary band-edge potentials or photochemical stability to be suitable candidates. Tungsten oxide (𝐸bg 2.8 eV) is a good candidate with absorption up to 𝜆≈440 nm and known photochemical stability. Thin films of tungsten oxide were prepared using an electrolytic route from peroxo-tungsten precursors. The tungsten oxide thin films were characterised by FESEM, Auger electron spectroscopy, and photoelectrochemical methods. The magnitude of the photocurrent response of the films under solar simulated irradiation showed a dependence on precursor used in the film preparation, with a comparatively lower response for samples containing impurities. The photocurrent response spectrum of the tungsten oxide films was more favourable than that recorded for titanium dioxide (TiO2) thin films. The WO3 photocurrent response was of equivalent magnitude but shifted into the visible region of the spectrum, as compared to that of the TiO2.